Silent active device tracking for MR‐guided interventional procedures. Issue 5 (31st December 2022) - Stehning, Christian; Krueger, Sascha; Weiss, Steffen; Smink, Jouke; Koken, Peter; Hindricks, Gerhard; Jahnke, Cosima; Paetsch, Ingo
Abstract : Purpose: To evaluate a silent MR active catheter tracking sequence that allows conducting catheter interventions with low acoustic noise levels. Methods: To reduce the acoustic noise associated with MR catheter tracking, we implemented a technique previously used in conventional MRI. The gradient waveforms are modified to reduce the sound pressure level (SPL) and avoid acoustic resonances of the MRI system. The efficacy of the noise reduction was assessed by software‐predicted SPL and verified by measurements. Furthermore, the quality of the catheter tracking signal was assessed in a phantom experiment and during interventional cardiovascular MRI sessions targeted at isthmus‐related flutter ablation. Results: The maximum measured SPL in the scanner room was 104 dB(A) for real‐time imaging, and 88 dB(A) and 69 dB(A) for conventional and silent tracking, respectively. The SPL measured at different positions in the MR suite using silent tracking were 65–69 dB(A), and thus within the range of a normal conversation. Equivalent signal quality and tracking accuracy were obtained using the silent variant of the catheter tracking sequence. Conclusion: Our results indicate that silent MR catheter tracking capabilities are identical to conventional catheter tracking. The achieved acoustic noise reduction comes at no penalty in terms of tracking quality or temporal resolution, improves comfort and safety, and can overcome the need for MR‐compatible communication equipment and background noise suppression during the actual interventional procedure.